SHEPHERDS OF THE VALLEY: THE ROLE OF CHOPANS IN KASHMIRI RURAL LIFE - Chopan, Taraiq Ahmad; Kumar, Tariq Ahmad; Rashid, Younus (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The rural social structure of Kashmir was typically marked by strong shared bonds, class stratification, and occupational reliance. Central to this structure were the peasants and other landless groups especially Chopans (shepherds) essential to agrarian life. While the peasants depended on agriculture and livestock for livelihood, the Chopans played a crucial role in sheep rearing and forest resource collection. Their relationship was reciprocal, with Chopans depending on peasants for livelihood, and peasants valuing Chopans for their services and benefactions to agriculture, soil fertility, and cultural life. Moreover, Chopans interconnected with non-agrarian occupational groups such as barbers and potters through a barter system linked in mutual dependence. This paper reveals how rural Kashmir’s socio-economic life was supported through deeply rooted customs, cooperation, and oral traditions, highlighting the Chopan community’s crucial role in the village ecosystem.